ГОТИКАЛЫҚ, МАГИЯЛЫҚ, БАРОККОЛЫҚ ТУЫНДЫЛАРДАҒЫ КЕЙІПКЕРЛЕР ЖҮЙЕСІ. - Сагидуллиева, С. С.; Оразбек, М. С.; Мухиева, Г. С. (Eurasian Journal of Philology: Science & Education, 2025)
In all genres of the title of a work of art, the hero is the author’s most important problem and image, acting with himself in conveying the world of the author’s thought. This article analyzes the world of characters in the works of baroque, gothic, magic in Kazakh-Hungarian literature. The motives of the duality of characters, ghosts and demons, the image of a corpse were differentiated based on a comparative textual analysis in the works published in the XIX-XXI century. The interrelation between the archetype and the psychology of the characters, the psychology of the author, the positive-negative trait and the gender character of the ghost image were considered. The typology of characters in the stories of A.Altai, M. Omarova, K. Mubarak, M. Malik, L. Konys, G. Dragomany, L.Darvashi was analyzed. The article analyzes the ways in which these authors convey the main idea of the author, preserving individuality, imagery, originality, revealing her national identity like no other in the character, actions, thoughts of the main character. Character is understood as the main reason for everything that happens in the life of a universal human being. The analysis of the structure of the hero and the narrator, the analysis of the image allows us to determine the author’s position, which is not directly reflected in the work. Hermeneutical and comparative methods were used in the study. In the interpretation of the term «hero», the system of images in genres works, the type of urban children, based on the conclusions of scientists, is proved by examples.